IFNL cytokines do not modulate human or murine NK cell functions - O'Farrelly, Cliona; Gardiner, Clair (My University, 2014)
The interferon-lambda (IFNL) cytokines have been shown to be important in HCV infection with SNPs in the IFNL3 gene associated with both natural and treatment induced viral clearance. We have recently shown that rs1299860 (an IFNL3 associated SNP) and an NK cell gene, KIR2DS3, synergised to increase the odds of chronic infection in a homogenous cohort of Irish women infected with HCV. To characterise a biological basis for the genetic synergy, we investigated for any evidence that IFNL cytokines regulate NK cell functions. Using a range of functional responses, we did not find any evidence of NK cell activation by IFNL3, IFNL1 or IFNL2 cytokines. Similar results were found using human and murine NK cells. In addition, and in contrast to our preliminary study, we did not find any evidence that IFNL cytokines inhibited NK cell cytokine production; thus, the biological basis for the genetic synergy remains to be discovered.
PUBLISHED
Keywords: Interferon lambda; HCV; NK cells